2018
DOI: 10.1021/acs.inorgchem.8b00976
|View full text |Cite
|
Sign up to set email alerts
|

Rebuilding C60: Chlorination-Promoted Transformations of the Buckminsterfullerene into Pentagon-Fused C60 Derivatives

Abstract: In recent years, many higher fullerenes that obey the isolated pentagon rule (IPR) were found capable of rearranging into molecules with adjacent pentagons and even with heptagons via chlorination-promoted skeletal transformations. However, the key fullerene, buckminsterfullerene I -C, long seemed insusceptible to such rearrangements. Now we demonstrate that buckminsterfullerene yet can be transformed by chlorination with SbCl at 420-440 °C and report X-ray structures for the thus-obtained library of non-IPR d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
52
0
6

Year Published

2019
2019
2020
2020

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 30 publications
(59 citation statements)
references
References 51 publications
(156 reference statements)
1
52
0
6
Order By: Relevance
“…X‐ray diffraction studies of chlorination products revealed eventual formations of non‐IPR or non‐classical chlorides due to, respectively, Stone‐Wales rearrangements (SWRs) or losses of C 2 fragments (C2Ls) from fullerene carbon cages . It was recently shown that C 60 is also capable to skeletal transformations when the interaction is carried out at harsher conditions of 420–440 °C . As the further development of the method, two‐stage process, a chlorination followed by trifluoromethylation (Cl/CF 3 ), was proposed .…”
Section: Figurementioning
confidence: 99%
See 2 more Smart Citations
“…X‐ray diffraction studies of chlorination products revealed eventual formations of non‐IPR or non‐classical chlorides due to, respectively, Stone‐Wales rearrangements (SWRs) or losses of C 2 fragments (C2Ls) from fullerene carbon cages . It was recently shown that C 60 is also capable to skeletal transformations when the interaction is carried out at harsher conditions of 420–440 °C . As the further development of the method, two‐stage process, a chlorination followed by trifluoromethylation (Cl/CF 3 ), was proposed .…”
Section: Figurementioning
confidence: 99%
“…). This type of chlorination‐promoted skeletal transformations has been reported for C 60 and some isomers of higher fullerenes such as C 76 (1), C 78 (2), and C 100 (18) . Usually, the SWR transformations occurred, if one or both carbon atoms of a rotating C−C bond are chlorinated.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…Wiedergabe mit Genehmigung aus f) Lit. , Copyright 2018 American Chemical Society; g) Lit. , Copyright 2011 Macmillan Publishers Limited; h) Lit.…”
Section: Stabilisierung Von Drei Miteinander Kondensierten Fünfringenunclassified
“…[116] Danach wurden die elektrochemischen Eigenschaften von #1809 C 60 Cl 8 untersucht und mit denen von #271 C 50 Cl 10 verglichen, was sein besonderes elektroaktives Polymerisationsverhalten aufzeigte,d as sich deutlich von dem der Chloride von I h -C 60 wie C 60 Cl 8 und C 60 Cl 10 unterschied. [117] Kürzlich synthetisierten Tr oyanov et al durch Anwendung einer Nachchlorierungsreaktion von I h -C 60 mit SbCl 5 drei neue Nicht-IPR-Chloride von C 60 -C 2v -#1810 C 60 Cl 24 , D 2d -#1805 C 60 Cl 24 und D 5 -#1794 C 60 Cl 20 -m it vier, vier bzw.f ünf DFP-Paaren (Abbildung 8e-g), zusammen mit einem nichtklassischen Nicht-IPR-Derivat von C 60 , [131] 66 in zwei Te ile, in einen halbkugelfçrmigen C 50 -Teil und einen benzolähnlichen C 6 -Ring mit sp 2 -Kohlenstoffatomen, wodurch die lokale Aromatizitätverringert werden kann. [36] Mit dem gleichen modifizierten Bogenentladungsverfahren mit CCl 4 synthetisierten und isolierten Xie et al außerdem C 68 Cl 6 .…”
Section: Angewandte Chemieunclassified